Beyond Crowns, Sashes, and Heels: Factors Associated with Self-esteem and Achievement Motivation among Local Beauty Pageant Candidates in the Philippines - Therese Cruz, Hanna (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
This paper explores the factors in a beauty pageant journey that are associated with the self-esteem and achievement motivation of local beauty pageant candidates.
Keywords: Beauty pageants; self-esteem; achievement motivation